Feminist Trouble Intersectional Politics in Postsecular Times - Lepinard, Eleonore (Oxford University Press, 2020)
For more than two decades Islamic veils, niqabs, burkinis, forced and arranged marriages, polygamy and Sharia rules concerning women have been the object of intense public scrutiny and legal regulations in many Western countries, especially in Europe, and feminists have been actively engaged on both sides of the debates. In Feminist Trouble, Eléonore Lépinard draws on extended fieldwork with numerous women's organizations in France and Quebec. Giving voice to women of color, Lépinard dissects hierarchies of privilege in feminist politics, grappling with Islam and Islamic veiling debates to understand how these changes have transformed contemporary feminist movements, intersectional politics, and the feminist collective subject. A critical look at feminism, its divisions, and its future, Feminist Trouble argues that feminism should not be centered around an identity-women-but should instead focus on a feminist ethic of responsibility that requires women to prioritize their ethical responsibility to the feminist project